Two new species of Macrobiotus (Eutardigrada, Macrobiotidae) from Tien Shan (Kirghizia), with notes on Macrobiotus tenuis group - Tumanov, Denis V. (Zootaxa, 2005)
An illustrated description of Macrobiotus barabanovi sp. nov. and Macrobiotus kirghizicus sp. nov. from Tien Shan (Kirghizia) is given. Macrobiotus barabanovi sp. nov. belongs to the harmsworthi group. It differs from the majority of species of this group in having very long claws. Macrobiotus kirghizicus sp. nov. is similar to M. ariekammensis in claw morphology, but differs clearly from this species in having differences in bucco-pharyngeal apparatus and characters of the egg processes. Based on the details of the claws structure, M. ariekammensis is excluded from the tenuis group of the genus Macrobiotus and grouped together with M. kirghizicus sp. nov. in the new ariekammensis group.